'Be global, go local' – innovation and creativity in the development of alternative guiding services in Budapest. Issue 5 (20th October 2017) - Rátz, Tamara
ABSTRACT: Based on qualitative research methods, the paper explores the emergence of creativity and innovation in the development of guiding services, and analyses the cultural and spatial characteristics of alternative guided tours developed for niche markets in Budapest, Hungary. The study is part of a 3-year (2011–2014) research programme entitled 'Creativity and its contribution to niche tourism development – following and creating trends' that aimed to investigate the potential of niche tourism products in the Hungarian market. In order to understand the development process, characteristics and significance of alternative guiding in the city, a complex methodology of interviews, participant observation and content analysis of service providers' websites and customers' feedback on social media sites was used. The analysis suggests that although the impact of these alternative guided tours on the city's tourist image is currently limited, they contribute to the repositioning of the destination and enrich its ambiance.